Participatory Rural Appraisal as a Legal Education for Prevention of Trademark Infringement (Case of Bandungan, Central Java, Indonesia) - Ridwan Arifin; Riska Alkadri; Bayangsari Wedhatami; Zainurohmah Zainurohmah; Nadiyah Meyliana Putri; Muhammad Wahyu Saiful Huda; Sukma Jati Husodo; Sinta Swasti (Universitas Negeri Semarang, 2023)
Trademarks play a crucial role in protecting the intellectual property rights of businesses and individuals. However, in rural and remote areas, awareness of trademark infringement and the legal mechanisms to prevent it may be limited. This study explores the use of Participatory Rural Appraisal (PRA) as an innovative approach to legal education in preventing trademark infringement, focusing on the case of Bandungan in Central Java, Indonesia. The research utilizes a mixed-methods approach, combining qualitative and quantitative data collection techniques. Through a series of workshops, surveys, and participatory activities, the study engages with the local community in Bandungan to assess their understanding of trademarks, identify potential infringement issues, and deliver legal education on trademark protection. The findings reveal that the PRA approach effectively enhances the community's awareness of trademark rights and the legal remedies available to prevent infringement. Participants actively participate in discussions, share their experiences, and collaboratively generate strategies to protect local businesses' intellectual property. Moreover, the study identifies specific challenges faced by the community in safeguarding trademarks, such as limited access to legal resources and awareness of the legal system. The research contributes to the field of legal education and rural development by highlighting the potential of PRA as a practical and community-driven method for raising awareness about trademark infringement prevention. It underscores the importance of tailoring legal education programs to the specific needs and contexts of rural communities, ultimately empowering them to protect their intellectual property rights and foster economic development.